Effect of neodymium addition on the structural, mechanical, and magnetic properties of FeCoNiCu(MnCr)0.5 high entropy alloys - Yayla, Nihal; Simsek, Telem; Boyrazli, Mustafa; Guler, Omer (Springer Heidelberg, 2025)
Neodymium (Nd), a rare earth element, was incorporated into the [FeCoNiCu(MnCr)0.5] high-entropy alloy (HEA) at weight percentages of 0.5%, 1%, 2%, and 5%. The alloys were synthesized successfully using the arc melting method. X-ray diffraction (XRD) analysis confirmed that both the undoped and Nd-doped alloys exhibit a single-phase solid solution with a face-centered cubic (FCC) crystal structure, consistent with thermodynamic predictions derived from the Miedema model. Scanning electron microscopy (SEM) revealed a dendritic structure in the undoped alloy, which was replaced by Cu- and Cr-rich regions in the 5% Nd-doped alloy, as confirmed by energy dispersive spectroscopy (EDS). Differential scanning calorimetry (DSC) indicated an endothermic peak in the undoped alloy and minor thermal responses in Nd-doped samples, without distinct phase transitions within the 0-800 degrees C range. Mechanical testing demonstrated substantial enhancements in both hardness and tensile strength with increasing Nd content. The 5% Nd-doped alloy exhibited the highest performance, achieving a Vickers hardness of 370 HV and a tensile strength of 1186 MPa. Magnetic testing indicated ferromagnetic behavior in all samples, with Nd additions significantly enhancing magnetic properties. Notably, the 5% Nd-doped alloy achieved a saturation magnetization (Ms) of 41 emu/g and a coercivity (Hc) of 6.3 Oe, highlighting improved magnetic softness and rapid magnetization loss characteristic of soft magnetic materials.
Keywords: FeCoNiCuMnCr; High entropy alloys; Rare earth elements; Neodymium; Arc melting; Mechanic and magnetic properties